Left ventricular mass index unveils differences in sympathetic nervous system activity between patients with MINOCA and Takotsubo syndrome. (14th October 2021) - Mantzouranis, M; Leontsinis, I; Sakalidis, A; Klettas, D; Dimitriadis, K; Thomopoulos, C; Dri, E; Ntalianis, A; Avramidis, D; Stougiannos, P; Patsourakos, N; Tousoulis, D; et al.
Abstract: Background/Introduction: Left ventricular mass index (LVMI) has been long established as an index of target organ damage. It has demonstrated a prognostic role in cardiovascular morbidity and mortality assessed using either echocardiography or cardiac magnetic resonance (CMR) under the prism of coronary artery disease, hypertension, diabetes mellitus, chronic kidney disease. On the other hand, it has shown a strong association with indices of sympathetic nervous system (SNS) activity. Purpose: The aim of our study is to investigate for potential associations between LVMI and indices of SNS among patients with a working diagnosis of MINOCA. Methods: Our study population consists of 50 patients [32% male; mean age: 61±12 years old; 50% hypertensives (HTN), 16% with history of diabetes mellitus (DM), 22% smokers] admitted with acute coronary syndrome (ACS) fulfilling the diagnostic criteria of MINOCA. A subsequent CMR demonstrated an ischemic pattern of late gadolinium enhancement (LGE) in 15 cases (27.8%), findings indicative of Takotsubo syndrome (TTS) in 19 patients (35.2%), whereas failed to reveal any abnormalities in 16 cases (29.8%). LVMI was estimated using left ventricular mass per body surface area (LV mass/BSA) as derived from CMR. SNS activity was assessed using muscle sympathetic nerve activity (MSNA) during the first 30 days of patient discharge. Results: Univariate analysis failed to demonstrate an association between LVMI and indices of SNS in the total population. This was found to be driven by the TTS group. However, for all other MINOCA cases (n=31; including both LGE CMR and clear CMR cases) LVMI demonstrated a significant positive association with MSNA measured as bursts/min (OR, 0.558; CI 95%, 0.200–0.915; p=0.004). A multivariate analysis was conducted in the same group in which LVMI retained its statistical significance independently of age, gender, ejection fraction derived from CMR, history of HTN and DM (OR, 0.518; CI 95%, 0.030 - 0.952; p=0.038). TTS group did not show any association between LVMI and MSNA. Conclusions: These preliminary results may imply an underlying mechanism of reverse negative feedback on systematic SNS activity after the acute phase of sympathetic overdrive during a TTS event. Further investigation is warranted to confirm our research findings. FUNDunding Acknowledgement: Type of funding sources: None.